Economic Monitoring Report to the Ad Hoc Liaison Committee - World Bank Group (World Bank, Washington, DC, 2019)
After a steady improvement in the fiscal position over the past decade, the standoff over clearance revenues has severely constrained the PA budget, leading to a significant expansion in expenditure arrears. Going forward, however, uncertainty about a resolution for the clearance revenue standoff will weigh on the economy. Over the last two decades, the Palestinian economy has been driven by large inflows of transfers as other sources of growth have been long-hindered by the ongoing Israeli restrictions on movement and access. Under a baseline scenario which assumes a continuation of the Israeli restrictions, persistence of the internal divide between the West Bank and Gaza and a decline in aid levels, the Palestinian economy is expected to slip into a recession in 2020 and 2021, even if additional, one-off transfers from clearance revenues are made. As financial buffers are depleted, the reduced revenues will require sizable cuts in public spending, which in turn would translate in reduced consumption and investment. The decline in growth implies a sizable decline in real per capita income and a rise in poverty. The Palestinian financial sector continues to face substantial risks against the backdrop of the fiscal crisis. The negative impact of the deepening fiscal crisis on the quality of loan portfolios across the banking sector has started to materialize as both non-performing loans and classified loans have been on an upward trajectory. With the severe liquidity shortage facing the PA, it has resorted to domestic banks to finance its needs raising the sector’s exposure to the PA for the first time in a number of years. Banks are also rescheduling outstanding loans held by PA employees who are receiving a reduced salary, compounding the destabilizing effect on the sector. However, the fact that the PA is simultaneously building up an asset in the form of tax revenues not received from the GoI ameliorates the situation as the increased exposure may be seen as a temporary trend. Another cause of concern is a possible disruption in Correspondent Banking Relationships (CBRs) between Palestinian banks and their Israeli counterparts due to de-risking by Israeli banks. The immunity and indemnity package given by the GoI to banks with CBRs are set to expire in May 2020 and February 2021, respectively, when a longer term and more sustainable intervention is expected to be in place. While resolving the fiscal crisis is an immediate priority there remains a broader reform agenda to improve the economy and Palestinian living standards.